Evaluation of Hepatic Impairment Dosing Recommendations in FDA‐Approved Product Labels. (7th July 2013) - Chang, Yang; Burckart, Gilbert J.; Lesko, Lawrence J.; Dowling, Thomas C.
Abstract Pharmacokinetic (PK) studies in patients with liver disease are an important clinical pharmacology component of drug development. In 2003, FDA released the guidance for industry on "Pharmacokinetics in Patients with Impaired Hepatic Function, " which provides recommendations to sponsors on study design, data analysis, and impact on dosing and labeling. We evaluated the quality and consistency of hepatic dosing recommendations, and compared contemporary clinical practice of dosing in patients with impaired hepatic function with product labels. All new molecular entities (NME) and labels approved by the FDA during the period of January 2004 to December 2011 were reviewed. The fraction of the dose hepatically eliminated, quality of hepatic impairment PK studies reported, and any dose recommendations provided in the label and in a tertiary clinical reference (Micromedex) were reviewed. Out of 157 NMEs, 67 met the criteria for evaluation of dosing in hepatic disease. Problem areas were identified related to the lack of specific hepatic metabolism information in 90% of FDA‐approved labels, inconsistent terminology, and "use with caution in liver disease" in 27% of NME. Updating the FDA guidance on PK studies in patients with impaired hepatic function could provide a standardized approach to improve the clinical usefulness of this dosing information for practitioners.